Pendekatan Deep Learning untuk Menciptakan Pengalaman Belajar yang Bermakna - Turmuzi, Ahmad (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The advancement of artificial intelligence technology, particularly deep learning, has opened new opportunities in education to create more meaningful learning experiences. This study aims to analyze how the deep learning approach can be applied in the learning process to enhance student engagement, comprehension, and learning outcomes. The research method used is qualitative with a library research or literature study approach. Data were obtained from various academic sources, including scientific journals, books, research reports, and relevant publications from the last five years. The findings indicate that the implementation of deep learning in education can improve the personalization of learning materials, provide adaptive feedback, and enrich learning experiences through AI-based systems such as chatbots, learning analytics, and gamification-based learning. Additionally, this technology enables more interactive learning by adapting curricula based on individual needs and learning styles. However, challenges in implementing deep learning in education still include access to technology, teacher readiness, and policies that support digital transformation in the education system. This study contributes to the literature on the application of deep learning in education and provides recommendations for educators, policymakers, and technology developers to optimize the use of artificial intelligence in creating more effective and meaningful learning experiences.